1998
DOI: 10.1097/00005537-199803000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of Anatomic Variations of Computed Tomography Scans of the Sinuses: A Surgeon's Perspective

Abstract: Four hundred computed tomography (CT) scans of patients undergoing endoscopic sinus surgery were studied with particular attention to anatomic variations. Six specific variations were identified that may predispose the surgeon to inadvertent penetration of the orbit or anterior cranial cavity. These anatomic variants are: 1. lamina papyracea lies medial to the maxillary sinus ostium; 2. maxillary sinus hypoplasia; 3. fovea ethmoidalis abnormalities, such as low or sloping fovea and encephaloceles; 4. lamina pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
109
1
7

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(119 citation statements)
references
References 5 publications
2
109
1
7
Order By: Relevance
“…In conclusion, considering the common sphenoid sinus anatomical variations, a detailed preoperative radiological evaluation is needed to ascertain a successful transsphenoidal surgical procedure (Meyers et al, 1998). However, the standard clinical radiological techniques might not be able to visualize all elements that may increase the risk of iatrogenic injury.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, considering the common sphenoid sinus anatomical variations, a detailed preoperative radiological evaluation is needed to ascertain a successful transsphenoidal surgical procedure (Meyers et al, 1998). However, the standard clinical radiological techniques might not be able to visualize all elements that may increase the risk of iatrogenic injury.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery requires awareness of the complexities of sinus anatomy and is made difficult by the high incidence of sinus anomalies. A recent study [4] indicated frequent variations on CT examination of 400 patients; 10% showed ethmoidal sinus hypoplasia, 4% maxillary sinus hypoplasia and incidences of 2-4% were noted for other gross anomalies. Another study [5] of 110 CT scans of patients suffering inflammatory sinus disease identified anomalies of the paranasal sinuses in 20% and further anomalies of the nasal septum and middle nasal concha in more than 55%.…”
Section: The Paranasal Sinuses: Clinical Significancementioning
confidence: 97%
“…13 Even though many studies reporting occurrence of low ESB causing complications during ESS exist [3][4][5][6][7][8][9] only limited studies have evaluated low ESB till date. 13,14 So the present study aims to evaluate and classify ESB preoperatively using coronal paranasal sinus CT scan images in Indian population and to deduce the relationship of ESB between side and gender. …”
Section: Introductionmentioning
confidence: 99%